Empathy in the Curriculum for Patient Care (2018)
Introduction: Empathy on nursing education is an important element in therapeutic communication and in the type of humanized care provided, due the strengthening of the nurse-patient relationship depends on this. Objective: To evaluate the levels of empathy on nursing students of a Higher Education Institution. Cartagena de Indias/Colombia. Material and Methods: Cross-sectional exploratory study. A sample of 320 nursing students from first to fourth year of training, to whom the Jefferson Medical Empathy Scale (JMES) was applied in the Spanish version. Results: Levels of empathy are reflected more in women than in men in general. However, some values vary with respect to the average at 3.14 levels in relation to the first year of schooling. Conclusion: The need for a curricular redesign and favoring empathic actions by professors worthy of being imitated by students as a way of encouraging empathy when caring for patients.